IT Infrastructure Assessment using the COBIT 2019 Framework - Aulia Faqih Rifa'i; Sumarsono; Muhammad Fauzan Al Baihaqi; Yazid Azfa Yasa (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
The Admission Office is responsible for student enrollment, and since 2013, the admission process at UIN Sunan Kalijaga has been supported by information technology. To assess the current state of the IT infrastructure in this university, the COBIT 2019 Framework was used. This study identifies five key domains in need of improvement: APO12 (manage risk), which focuses on managing IT-related risks within an organization, BAI10 (manage configuration), to ensure that IT services are delivered efficiently and effectively, DSS02 (manage service requests & incidents), involves the process of providing quick and efficient responses to user requests and handling various incidents, DSS03 (manage problems), to provide timely and effective support to consumers, ensuring their issues are addressed, their needs are met, and DSS04 (manage continuity), to ensure that the organization can respond effectively to incidents and disruptions, minimizing downtime and maintaining business continuity. The results showed that the capability levels for these domains in UIN Sunan Kalijaga were at Level 1, while the target was Level 4, leading to a capability gap of 3. The gap indicates that considerable effort is required to improve and achieve the desired level of maturity, and this research proposes some recommendations to improve the IT infrastructure.